Acetazolamide-Triggered Acute Flaccid Paralysis and Toxic-Metabolic Encephalopathy in a Toddler with Gastroenteritis: A Case Report - Green, Jack; Nawathe, Pooja (Journal of Child Science, 2020)
Acetazolamide is an infrequently prescribed medication in the outpatient pediatric setting, as one of its major indications is for the treatment of glaucoma, which is a largely adult disease. Though incredibly rare, serious neurologic side effects such as stroke, flaccid paralysis, and coma can occur after its administration. This case presentation of acute flaccid paralysis with metabolic derangement underscores the unusual, yet possible, toxic-metabolic and neurologic sequelae that can occur in an already acidotic host (in this case, caused by gastroenteritis) with acetazolamide ingestion. Life-threatening conditions must always be ruled out in patients who present with encephalopathy, but a medication history was crucial in clinching this case's unifying diagnosis. While there are case reports highlighting the rare central nervous system toxicities associated with acetazolamide ingestion, to our knowledge, none exist in the pediatric literature.
Keywords: encephalopathy; metabolic derangement; ketotic hypoglycemia; dehydration